FACTORS ASSOCIATED WITH KNOWLEDGE, PERCEPTION, AND PRACTICE TOWARD SELF-CARE AMONG ELDERLY PATIENTS SUFFERING FROM TYPE 2 DIABETES MELLITUS IN RURAL THAILAND - Eknithiset, Rapat; Somrongthong, Ratana; Kumar, Ramesh (Journal of Ayub Medical College Abbottabad, 2017)
Background: Globally, diabetes caused 4.6 million deaths during 2011 and burdened health care systems worldwide with $465 billion. The diabetes prevalence rate in Thailand has risen dramatically in recent years, from just 2.3% in 1991 to 6.9% in 2009. The objective of this study was to explore factors associated with knowledge, perception, and practice toward self-care among elderly type 2 diabetes mellitus patients aged 50-70 years. Methods: A cross sectional study design was conducted by enrolling 140 aged people of both gender suffering from type 2 diabetes mellitus and registered at three clinics of Primary healthcare at Taladnoi, Horathep, and Khokyai, Saraburi, Thailand. Participants whose age was 50-70 were rechecked through laboratory testing like Hba1c, FBS, and BMI were included. Data was analysed by using descriptive statistics and chi-square. Results: The participants mean age was 62.11±0.59 years and 69.4% were female, 27.8% belonged to indigenous caste and 82.6% were married. About one-fourth of the participants were housewives, 15.2% government employee and 12.1% were farmer. Participants suffering from diabetes since1-5 years were 48.5%. Among the diabetic patients, 51.5% reported to have family history of diabetes. The mean knowledge score of the respondents was 3.61 (±1.80), perception was 4.34 (±1.41), practice was 12.14 (±4.47). A significant different existed between gender with Hba1c (<0.05), knowledge, and work status with Hba1c (<0.05). Conclusion: Study concluded that the knowledge, perception, and practice about type 2 diabetes mellitus among patient were significantly poor. However, the factors like; gender, work and practice were found significantly correlated with glycated haemoglobin. Keywords: Diabetes Mellitus Type 2; Knowledge; Perception; self-care; elderly population and associated factors